Número de cromosomas de Chenopodium quinoa Willd. en radículas y raicillas - Gandarillas, H.; Luizaga, J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The chromosomes of quinoa (Chenopodium quinoa Willd.) were counted in radicles and root tips. Polyploidy was found in the radicles varying from 18 to 36 chromosomes. This would indicate that the radicles possessing 18 and 27 chromosomes had a reduced number. Endopolyploidy was also found with a chromosome number surpassing heptaploidy. These results indicate that during the germination of the seed and in the first stage of plant life, reduction and posterior polyploidy would be a normal processes. A constant number of 36 chromosomes was found in the root tips